PERAN DAN TANTANGAN MAHKAMAH KONSTITUSI DALAM MENEGAKKAN SUPREMASI KONSTITUSI DI INDONESIA - Aura Zabina Rassel; H. Rusdianto; M. Budhi Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
The Constitutional Court plays a crucial role in upholding constitutional supremacy and enforcing the principles of the rule of law in Indonesia through its judicial review authority. As the guardian of the constitution, the Court ensures that regulations enacted by the legislative and executive branches remain aligned with the 1945 Constitution while protecting the fundamental rights of citizens. This study employs a qualitative approach with a literature review method to analyze the roles, authorities, and challenges faced by the Constitutional Court. The findings indicate that although the Court's decisions are final, binding, and applicable erga omnes, their effective implementation still faces serious obstacles. Major challenges include a lack of harmonization between Court rulings and existing legislation, weak commitment from legislative and executive bodies to follow up on decisions, and complexity in field execution. In conclusion, a stronger mechanism for decision implementation is required to guarantee legal certainty and create a more just, democratic, and constitutionally compliant state system.